The Effect of Types of Fruit Skin Extracts as Carotenoid Suppliers on Color Brightness of Koi Fish - Henry Sinaga; Maretty TD Butarbutar (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
The koi fish (Cyprinuscarpio) have unique in part of body color. Fruit peel which is considered asagricultural waste needed to be managed to increase the selling value. The research aimed to determine theeffect of carrot peel extract and dragon fruit peel extract as carotenoid suppliers on the color brightness ofkoi fish. The treatments tested were the parameters measured in the form of color brightness, survival,growth and water quality. Analysis of the data used is ANOVA, if the results are significantly differentthen the smallest significant difference test (BNT) and water quality analysis are descriptive. The resultsshowed that the fruit peel extract had a significant effect on the brightness of the color of koi fish seeds.The best value of color change, survival and growth in treatment 3 with the addition of carrot peel extract.The result of this research showed that the fruit peel extract had a significant effect on the brightness ofthe color of koi fish seeds.